Viscosity modifier, liquid composition and viscosity control method thereof, ink and inkjet printer
By using polymer nanofibers with core shell structure and controlling their viscosity characteristics by temperature changes, the problem of small viscosity changes under temperature conditions in the prior art is solved, and flexible adjustment of liquid viscosity is achieved.
Patent Information
- Application Number
- JP2023163231
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
AI Technical Summary
In the prior art, the viscosity variation range of cellulose nanofiber is smaller due to changes in temperature conditions, making it difficult to effectively control the viscosity.
The polymer nanofibers with a core shell structure are used, the core is a phosphate group and the shell is a hydrophilic resistance polymer. The hydrophilic resistance polymers formed by self-assembly are used, and the viscosity characteristics of the polymer nanofibers formed by self-assembly vary with temperature and are controlled based on the glass transition temperature.
The effect of controlling viscosity characteristics through temperature changes is achieved, and the viscosity of liquid can be effectively adjusted under different temperature conditions, and is suitable for various liquid compositions and inks.
Smart Images

Figure 2025054053000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a viscosity modifier, a liquid composition and a method for adjusting the viscosity thereof, an ink, and an ink-jet printer. [Background technology]
[0002] Patent Document 1 discloses that the viscosity of a slurry containing cellulose nanofibers changes depending on the shear rate conditions. In a slurry containing cellulose nanofibers, the shear viscosity increases when the shear rate is low, whereas the shear viscosity decreases when the shear rate is high. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 111165 Summary of the Invention [Problem to be solved by the invention]
[0004] However, since the range of change in viscosity of cellulose nanofiber due to changes in temperature conditions is small, it is difficult to control the viscosity by changing the temperature conditions. The present invention provides a viscosity modifier whose viscosity characteristics can be controlled by changing temperature conditions. [Means for solving the problem]
[0005] The present invention has the following aspects. [1] A viscosity modifier comprising polymer nanofibers having a core-shell morphology with a lyophobic core and a lyophilic shell, the viscosity characteristics of which change when the temperature conditions are changed based on the glass transition temperature of the lyophobic core. [2] The viscosity adjuster according to [1], wherein the polymer nanofiber is formed by self-assembly of an amphiphilic block copolymer having a lyophilic block and a lyophilic block. [3] The viscosity modifier according to [2], wherein the lyophobic block has at least one selected from the group consisting of units based on styrene, units based on n-butyl (meth)acrylate, units based on methyl (meth)acrylate, and units based on benzyl (meth)acrylate. [4] The viscosity modifier according to any one of [1] to [3], wherein the polymer nanofibers are crosslinked. [5] A liquid composition comprising the viscosity modifier according to any one of [1] to [4] and a liquid medium. [6] A method for adjusting the viscosity of the liquid composition described in [5], comprising changing temperature conditions based on the glass transition temperature of the lyophobic core to change the viscosity characteristics of the liquid composition. [7] The viscosity adjusting method according to [6], further comprising changing the viscosity of the liquid composition by changing shear force conditions. [8] An ink containing the viscosity modifier according to any one of [1] to [4]. [9] The ink according to [8], which is for use in an inkjet printer.
[10] An inkjet printer comprising the ink described in [9]. Effect of the Invention
[0006] According to the present invention, there is provided a viscosity modifier whose viscosity characteristics can be controlled by changing temperature conditions. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram of an example of a polymer nanofiber. [Diagram 2] FIG. 2 is a schematic diagram showing amphiphilic block copolymers self-assembling to form polymer nanofibers. [Diagram 3] FIG. 3 shows the shear viscosity characteristics of the sample containing the polymer nanofibers of Example 1. [Figure 4] FIG. 4 shows the shear viscosity characteristics of the sample containing the polymer nanofibers of Example 2. [Diagram 5] FIG. 5 shows the shear viscosity characteristics of the sample containing the polymer nanofibers of Example 3. [Figure 6] FIG. 6 shows the shear viscosity characteristics of the sample containing the polymer nanofibers of Example 4. [Figure 7] FIG. 7 shows the shear viscosity characteristics of the sample containing the polymer nanofibers of Example 5. [Figure 8] FIG. 8 shows the shear viscosity characteristics of the sample containing the polymer nanofibers of Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] As used herein, the following terms have the following meanings: "(Meth)acrylic" is a general term for acrylic and methacrylic. "Lyophobic" refers to a property of having a relatively low affinity for a solvent and being prone to agglomeration with each other. The term "solvent affinity" refers to the property of having a relatively high affinity for a solvent and being easily compatible with the solvent. The symbol "~" indicating a range of numerical values means that the numerical values before and after it are included as the lower limit and upper limit.
[0009] [Viscosity modifier] One aspect of the present invention relates to a viscosity modifier. The viscosity modifier contains polymer nanofibers, and the polymer nanofibers have a core-shell structure having a lyophobic core and a lyophilic shell. The viscosity of the viscosity modifier changes when the temperature conditions are changed based on the glass transition temperature of the lyophobic core. The temperature conditions referred to here mean the temperature when the viscosity modifier is heated or cooled.
[0010] For example, as shown in the results of Figure 7 in the Examples described later, when the measurement temperature is higher than the glass transition temperature of the lyophobic core of the polymer nanofiber, the viscosity of the viscosity modifier tends to decrease as the measurement temperature increases. Therefore, when the measurement temperature is higher than the glass transition temperature of the lyophobic core of the polymer nanofiber, it is easy to maintain a relatively low viscosity state.
[0011] On the other hand, when the measurement temperature is lower than the glass transition temperature of the lyophobic core of the polymer nanofiber, the change in viscosity is smaller than when the measurement temperature is higher than the glass transition temperature of the lyophobic core of the polymer nanofiber. In other words, the viscosity is less likely to change even when the measurement temperature is higher. Therefore, when the measurement temperature is lower than the glass transition temperature of the lyophobic core of the polymer nanofiber, it is easier to maintain a relatively high viscosity state.
[0012] For example, the polymer nanofiber 10 shown in FIG. 1 has a core-shell morphology having a lyophobic core 20 and a lyophilic shell 30. The core-shell morphology in which multiple lyophilic shells 30 are attached to the surface of the fibrous lyophobic core 20 in a corona shape is shown in FIG.
[0013] The polymer nanofiber 10 shown in Fig. 1 is formed by the self-assembly of multiple amphiphilic block copolymers 1 having a lyophobic block 2 and a lyophilic block 3 as shown in Fig. 2. This self-assembly is sometimes called PISA (Polymerization-induced self-assembly).
[0014] The lyophobic block 2 may have only units based on one type of monomer, or may have units based on multiple types of monomers. The lyophilic block 3 may also have only units based on one type of monomer, or may have units based on multiple types of monomers. That is, the lyophobic block 2 and the lyophilic block 3 may each be a homopolymer or a copolymer. Typically, the polymer compositions of the lyophobic block 2 and the lyophilic block 3 are different from each other, but are not particularly limited.
[0015] The constituent monomers of the lyophobic block 2 and the lyophilic block 3 can be appropriately selected from various monomers by a person skilled in the art so as to exhibit the desired lyophobicity and lyophilicity, respectively. Suitable monomers for forming the polymer nanofiber 10 include, for example, monomers represented by the following formula (1).
[0016] [ka]
[0017] In formula (1), H is a hydrogen atom. In formula (1), U and W are each independently -COOH, -COOR 1 , -COR 1 , -CSR 1 , -CSOR 1 , -COSR 1 , -CONH2, -CONHR 1 , -CONR 1 2. At least one selected from the group consisting of a hydrogen atom, a halogen atom, and an alkyl group having 1 to 4 carbon atoms which may have a substituent, or U and W are bonded to each other to form a cyclic ester which may have a substituent, an acid anhydride group which may have a substituent, or an imide ring which may have a substituent.
[0018] The substituents referred to here are hydrogen atoms, -COOH, -COOR 1 , -COR 1 , -CSR 1 , -CSOR 1 , -COSR 1 , -CN, -CONH2, -CONHR 1 , -CONR 1 2, -OR 1 , -SR 1 , -OOCR 1 , -SCOR 1 , and OCSR 1 At least one selected from the group consisting of:
[0019] In formula (1), V is a hydrogen atom, R 1 , -COOH, -COOR1 , -COR 1 , -CSR 1 , -CSOR 1 , C.O.S.R. 1 , -CONH2, -CONHR 1 , -CONR 1 2, -OR 1 , -SR 1 , -OOCR 1 , -SCOR 1 , and -OCSR 1 At least one selected from the group consisting of:
[0020] R 1 each independently represents at least one selected from the group consisting of an alkyl group which may have a substituent, an alkenyl group which may have a substituent, an alkynyl group which may have a substituent, an aryl group which may have a substituent, a heteroaryl group which may have a substituent, a carbocyclyl group which may have a substituent, a heterocyclyl group which may have a substituent, an arylalkyl group which may have a substituent, a heteroarylalkyl group which may have a substituent, an alkylaryl group which may have a substituent, an alkylheteroaryl group which may have a substituent, and a polymer chain which may have a substituent.
[0021] R 1 Examples of the optional substituent include, but are not limited to, an epoxy group, a hydroxy group, an alkoxy group, an acyl group, an alkylcarbonyl group, a carboxy group, a sulfonic acid group, an isocyanate group, a cyano group, a silyl group, an amino group, salts thereof, and derivatives thereof.
[0022] Examples of polymer chains include, but are not limited to, polyalkylene oxides, polyarylene ethers, and polyalkylene ethers.
[0023] Non-limiting examples of monomers include, for example, maleic anhydride, N-alkylmaleimide, N-allylmaleimide, dialkyl fumarate, (meth)acrylic acid esters, (meth)acrylic styrene, (meth)acrylamide, (meth)acrylonitrile, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, (meth)acrylic acid, and butyl (meth)acrylate. benzyl, phenyl (meth)acrylate, α-methylstyrene, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, triethylene glycol (meth)acrylate, itaconic anhydride, itaconic acid, glycidyl (meth)acrylate, N-methyl (meth)acrylamide, N,N-Dimethyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, N-Methylol(meth)acrylamide, N-Ethylol(meth)acrylamide, Vinylbenzoic acid, Diethylaminostyrene, α-Methylvinylbenzoic acid, Diethylaminoα-Methylstyrene, p-Vinylbenzenesulfonic acid, Sodium p-Vinylbenzenesulfonic acid, Trimethoxysilylpropyl(meth)acrylate, Triethoxysilylpropyl(meth)acrylate, Tributoxysilylpropyl(meth)acrylate, Dimethoxymethylsilylpropyl(meth)acrylate, Dibutoxymethylsilylpropyl(meth)acrylate ) acrylate, dibutoxymethylsilylpropyl (meth)acrylate, dimethoxysilylpropyl (meth)acrylate, diethoxysilylpropyl (meth)acrylate, dibutoxysilylpropyl (meth)acrylate, diisopropoxysilylpropyl (meth)acrylate, diisopropoxymethylsilylpropyl (meth)acrylate, vinyl acetate, vinyl butyrate, vinyl benzoate, vinyl chloride, vinyl fluoride, vinyl bromide, maleic anhydride, N-phenylmaleimide, N-butylmaleimide, N-vinylpyrrolidone, N-vinylcarbazole, butadiene, ethylene, chloroprene, and styrene.
[0024] In a preferred example, the monomers are selected so that the lyophobic core has at least one selected from the group consisting of units based on styrene, units based on n-butyl (meth)acrylate, units based on methyl (meth)acrylate and units based on benzyl (meth)acrylate.
[0025] In one example, the philic block of the amphiphilic block copolymer can be prepared from at least one monomer selected from the group consisting of poly(ethylene glycol) methyl ether acrylate (PEGA), poly(ethylene glycol) methyl ether methacrylate (PEGMA), and (meth)acrylic acid, in which case the philic block has at least one selected from the group consisting of PEGA-based units, PEGMA-based units, and (meth)acrylic acid-based units.
[0026] In one example, the lyophobic block of the amphiphilic block copolymer may be prepared from at least one monomer selected from the group consisting of styrene, n-butyl (meth)acrylate, methyl (meth)acrylate, and benzyl (meth)acrylate, in which case the lyophobic block has at least one selected from the group consisting of units based on styrene, units based on n-butyl (meth)acrylate, units based on methyl (meth)acrylate, and units based on benzyl (meth)acrylate.
[0027] The number average molecular weight of the amphiphilic block copolymer is not particularly limited, but may be, for example, within the range of 5,000 to 100,000. The number average molecular weight of the amphiphilic block copolymer is a value calculated by converting the value measured by gel permeation chromatography (GPC) into a standard polystyrene equivalent value.
[0028] The glass transition temperature of the lyophobic core can be adjusted by the monomer composition of the lyophobic block. The glass transition temperature of the lyophobic core is appropriately selected depending on the application of the viscosity modifier, and is not particularly limited, but may be, for example, within the range of -70°C to 100°C. The glass transition temperature of the lyophobic core of the polymer nanofiber is measured as the glass transition temperature of the lyophobic block of the amphiphilic block copolymer forming the polymer nanofiber, which is a value calculated by the relational expression of the glass transition temperature Tg (°C) of the copolymer according to the following Fox equation.
[0029] 1 / (273+Tg)=Σ{W i / (273+Tg i )} W i : mass fraction of monomer i Tg i : Tg (℃) of homopolymer of monomer i The glass transition temperature of the homopolymer is a value using the values described in "Polymer Handbook, 4th Edition, John Wiley & Sons."
[0030] The fiber length of the polymer nanofibers is not particularly limited, but may be within the range of 5 nm to 2 mm, for example. The fiber width of the polymer nanofiber is not particularly limited, but can be within the range of 1 nm to 250 nm, for example. The ratio of fiber length to fiber width of the polymer nanofiber is not particularly limited, but may be within the range of 5 / 1 to 200,000 / 1, for example. The fiber length and fiber width of the polymer nanofibers are values determined by images observed with a transmission electron microscope (TEM).
[0031] The amphiphilic block copolymers that form polymer nanofibers by PISA can be synthesized by RAFT polymerization. RAFT stands for Reversible Addition-Fragmentation chain Transfer, a type of living radical polymerization method. PISA via RAFT makes it easy to form polymer nanofibers from amphiphilic block copolymers.
[0032] RAFT polymerization can be applied to most monomers that undergo radical polymerization by appropriately selecting a chain transfer agent (RAFT agent) depending on the monomer and reaction conditions. For example, when preparing an amphiphilic block copolymer in the presence of a chain transfer agent, the terminals of the growing blocks are endowed with specific functionality that controls the growth of the blocks by reversible deactivation radical polymerization (RDRP). The functionality of the terminals of the blocks here refers to the property that allows the formation of covalent bonds between ethylenically unsaturated monomers by reactivating the growing blocks in the second or third stage of the polymerization process.
[0033] The amphiphilic block copolymer forming the polymer nanofiber is preferably a polymer synthesized by RAFT polymerization. Details of RAFT polymerization are described in, for example, Polymer, 2008, volume 49, 1079-1131, Chemical Society Reviews, 2014, volume 43, 496-505, Macromolecules, 1998, volume 31, 5559-5562, Polymer, 2013, volume 54, 2011-2019, the contents of which are incorporated herein by reference.
[0034] In the RAFT polymerization of the amphiphilic block copolymers, a radical initiator may be used, selected to ensure an adequate half-life at the polymerization temperature sufficient to initiate the polymerization reaction. Examples of the radical initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-cyanobutane), 2,2'azobis(isobutyric acid) dimethyl, 4,4'-azobis(4-cyanovaleric acid), 4,4'-azobis-(4-cyanopentanoic acid), 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 1,1'-azobis(cyclohexanecarbonitrile), 2-(t-butylazo)-2-cyanopropane, 2,2'-azobis {2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl))propionamide], 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl) 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-ethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis(isobutylamide) dihydrate, 2,2'-azobis(2,2,4-trimethylpentane), 2,2'-azobis(2-methylpropane), t-butylperoxyacetic acid, t-butylperoxybenzoic acid, Examples of peroxynitrite include, but are not limited to, t-butyl peroxyneodecanoate, t-butyl peroxyisobutyrate, t-amyl peroxypivalate, t-butyl peroxypivalate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, dicumyl peroxide, dibenzoyl peroxide, dilauroyl peroxide, potassium peroxydisulfate, ammonium peroxydisulfate, di-t-butyl hyponitrite, and dicumyl hyponitrite.
[0035] In the RAFT polymerization of the amphiphilic block copolymer, a chain transfer agent may be used.Details of the chain transfer agent are described in paragraphs
[0046] to
[0057] of International Publication No. 2023 / 102600, the contents of which are incorporated herein by reference.
[0036] In one example, the polymer nanofiber may be crosslinked. The polymer nanofiber may be stabilized by crosslinking two or more amphiphilic block copolymers with a crosslinking agent. The crosslinking agent is not particularly limited, and various crosslinking agents can be used. For example, when the monomer material contains (meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol dimethacrylate, etc. can be used as the crosslinking agent. Details of the crosslinking agent are described in paragraphs
[0105] to
[0111] of WO 2023 / 102600, the contents of which are incorporated herein by reference.
[0037] The conditions of RAFT polymerization of the amphiphilic block copolymer forming the polymer nanofiber are appropriately selected by a person skilled in the art depending on the polymerization initiator, the type and amount of monomer used, and the polymerization medium. Details of the conditions of the RAFT polymerization are described in paragraphs
[0080] to
[0091] of International Publication No. 2023 / 102600, the contents of which are incorporated herein by reference.
[0038] (Action and effect) The viscosity modifier described above contains polymer nanofibers having a core-shell structure with a lyophobic core and a lyophilic shell, and therefore, as shown in the examples described later, the viscosity characteristics can be changed by changing the temperature conditions based on the glass transition temperature of the lyophobic core.
[0039] [Application example] (Liquid composition) The liquid composition contains the above-mentioned viscosity modifier and a liquid medium. The liquid composition may be a solution in which the viscosity modifier is dissolved in the liquid medium, or a dispersion in which the viscosity modifier is dispersed in the liquid medium.
[0040] The liquid medium may be an aqueous medium or an organic solvent. The liquid medium may be a mixture of two or more compatible liquid media. For example, the liquid medium may be a mixture of a water-soluble organic solvent and water, or a mixture of two or more organic solvents.
[0041] The organic solvent is not particularly limited, but examples thereof include γ-butyrolactone, acetone, methyl ethyl ketone, hexane, heptane, octane, 2-heptanone, cycloheptanone, cyclohexanone, cyclohexane, methylcyclohexane, ethylcyclohexane, methyl-n-pentyl ketone, methyl isobutyl ketone, methyl isopentyl ketone, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, ethylene glycol monoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoacetate, diethylene glycol diethyl ether, propylene glycol monoacetate, dipropylene glycol monoacetate, propylene glycol diacetate, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate. , propylene glycol monoethyl ether acetate, cyclohexyl acetate, ethyl 3-ethoxypropionate, dioxane, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, anisole, ethyl benzyl ether, cresyl methyl ether, diphenyl ether, dibenzyl ether, phenetole, butyl phenyl ether, benzene, ethylbenzene, diethylbenzene, pentylbenzene, isopropylbenzene, toluene, xylene, cymene, mesitylene, methanol, ethanol, isopropanol, butanol, methyl monoglycidyl ether, ethyl monoglycidyl ether, dimethylformamide, mineral spirits, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and various silicone oils.
[0042] The content of the viscosity modifier is preferably from 0.1 to 20 mass %, more preferably from 0.5 to 10 mass %, of the total amount of the liquid composition.
[0043] In the liquid composition, the viscosity characteristics can be changed by changing the temperature conditions based on the glass transition temperature of the lyophobic core of the polymer nanofiber of the viscosity modifier. When the temperature of the liquid composition is higher than the glass transition temperature of the lyophobic core, the higher the temperature of the liquid composition, the lower the viscosity of the liquid composition under a certain shear force condition. On the other hand, when the temperature of the liquid composition is higher than the glass transition temperature of the lyophobic core, the lower the temperature of the liquid composition, the higher the viscosity of the liquid composition under a certain shear force condition. Thus, the higher the temperature of the liquid composition is above the glass transition temperature of the lyophobic core of the polymer nanofiber of the viscosity modifier, the lower the viscosity of the liquid composition under a given shear condition, where the shear condition refers to the shear force and shear rate externally applied to the liquid containing the viscosity modifier.
[0044] In the method for adjusting the viscosity of the liquid composition, the viscosity of the liquid composition is changed by changing the temperature conditions based on the glass transition temperature of the lyophobic core. For example, when the temperature of the liquid composition is higher than the glass transition temperature of the lyophobic core of the polymer nanofiber, the viscosity tends to decrease as the measurement temperature increases. When the temperature of the liquid composition is higher than the glass transition temperature of the lyophobic core of the polymer nanofiber, it is easy to maintain a relatively low viscosity state. On the other hand, when the temperature of the liquid composition is lower than the glass transition temperature of the lyophobic core of the polymer nanofiber, the change in viscosity is smaller than when the temperature of the liquid composition is higher than the glass transition temperature of the lyophobic core of the polymer nanofiber. When the temperature of the liquid composition is lower than the glass transition temperature of the lyophobic core of the polymer nanofiber, it is easier to maintain a relatively high viscosity state.
[0045] In addition to the above-mentioned temperature conditions, the viscosity of the liquid composition can also be changed by changing the shear force conditions. For example, the viscosity of the liquid composition under a constant temperature condition decreases as the shear rate applied to the liquid composition increases, and increases as the shear rate applied to the liquid composition decreases.
[0046] (ink) The viscosity characteristics of the viscosity modifier of the present invention are consistent with the characteristics required for various inks, and therefore it is useful to use the viscosity modifier for inks, particularly inkjet printers. In particular, in inks for inkjet printers, low viscosity is preferred from the viewpoint of ejection properties, while high viscosity is preferred from the viewpoints of resolution and prevention of bleeding on paper.
[0047] According to the ink containing the viscosity modifier of the present invention, when the temperature conditions are higher than the glass transition temperature of the lyophobic core of the polymer nanofiber, the ink is likely to maintain a low viscosity state. On the other hand, when the temperature conditions are lower than the glass transition temperature of the lyophobic core of the polymer nanofiber, the ink is likely to maintain a high viscosity state. Therefore, the ink containing the viscosity modifier of the present invention is particularly suitable for use as an ink for inkjet printers. In the inkjet printer, the ink containing the viscosity modifier of the present invention is stored in an ink tank.
[0048] The components of the ink other than the viscosity modifier are not particularly limited, but may include, for example, a colorant, water, a colorant, a penetrant, an anti-drying agent, a pH adjuster, a preservative, and an anti-fungal agent. The colorant may be a pigment or a dye, and various dyes may be used.
[0049] Although several embodiments have been described above, the present invention is not limited to the embodiment examples disclosed in this specification, and can be appropriately modified and implemented without departing from the gist of the invention. The embodiments disclosed in this specification can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. EXAMPLES
[0050] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following description.
[0051] [Abbreviation] ·AA: Acrylic acid ·MAA: Methacrylic acid St: styrene ·BA: Butyl acrylate ·BzMA: Benzyl methacrylate PEGA: Poly(ethylene glycol) methyl ether acrylate PEGMA: Poly(ethylene glycol) methyl ether methacrylate BTPA: 2-(butylthiocarbonothioylthio)propanoic acid (product of Boron Molecular Corporation) CTDPA: 4-cyano-4-(dodecylthiocarbonothioylthio)pentanoic acid (Tokyo Chemical Industry Co., Ltd.: product code C3546) EGDA: Ethylene glycol diacrylate EGDMA: Ethylene glycol dimethacrylate ACPA: 4,4'-azobis(4-cyanopentanoic acid) M1: Phillips block 1 that forms the phillips shell (copolymer composition: AA / PEGA = 50 / 50 (molar ratio)) M2: Phillips block 2 that forms the phillips shell (copolymer composition: MAA / PEGMA=50 / 50 (molar ratio)) HEC1: Hydroxyethyl cellulose (Tokyo Chemical Industry Co., Ltd.: Product code H0242) HEC2: Hydroxyethyl cellulose (Tokyo Chemical Industry Co., Ltd.: Product code H0418)
[0052] [Preparation of M1] M1 used in each example was synthesized as follows. AA and PEGA were charged in a reaction vessel at a molar ratio of 50 / 50, and water was added to make the solid content 20% by mass. Then, BTPA and ACPA were added to make the monomer / BTPA / ACPA=44 / 1 / 0.1 (molar ratio), and nitrogen bubbling was performed for 30 minutes in an ice bath. After that, the reaction vessel was immersed in an oil bath at 80°C, and polymerization was performed for 3 hours while stirring to obtain an aqueous solution of M1. The number average molecular weight of M1 was 12,400.
[0053] [Preparation of M2] M2 used in each example was synthesized as follows. MAA and PEGMA were charged in a reaction vessel at a molar ratio of 50 / 50, and water was added to make the solid content 17 wt%. Next, CTDPA and ACPA were added to make the molar ratio of monomer / CTDPA / ACPA = 30 / 1 / 0.2, and nitrogen bubbling was performed for 30 minutes in an ice bath. The reaction vessel was then immersed in an oil bath at 80°C, and polymerization was performed for 3 hours with stirring to obtain an aqueous solution of M2. The number average molecular weight of M2 was 18,900.
[0054] [Example 1] The amphiphilic block copolymer forming the polymer nanofiber of Example 1 was synthesized as follows. M1, St, BA, ACPA, and NaHCO3 were charged into a reaction vessel in the molar ratio shown in Table 1, and water was added so that the solid content was 20% by mass. Then, a 1M aqueous solution of sodium hydroxide was added to adjust the pH of the solution to the value shown in Table 1, and nitrogen bubbling was performed for 30 minutes in an ice bath. Thereafter, the reaction vessel was immersed in an oil bath at 80°C, and polymerization was performed for 6 hours with stirring to obtain the polymer nanofiber of Example 1 in which the amphiphilic block copolymer was self-assembled.
[0055] [Example 2] Polymer nanofibers of each example were obtained in the same manner as in Example 1, except that the copolymerization compositions of the lyophilic block and the lyophobic block were changed and a crosslinking agent was used as shown in Table 1. Regarding the synthesis of polymer nanofibers, the copolymerization compositions (unit: eq) shown in Table 1 are values converted into molar ratios.
[0056] [Examples 3 to 5] Polymer nanofibers of each example were obtained in the same manner as in Example 1, except that the copolymerization composition of the lyophilic block and the lyophobic block was changed as shown in Table 1, and the crosslinking agent was added after the time shown in Table 1 had elapsed.
[0057] [Example 6] Polymer nanofibers of each example were obtained in the same manner as in Example 2, except that the copolymerization composition of the lyophilic block and the lyophobic block was changed as shown in Table 1, and the crosslinking agent was changed.
[0058] [Comparative Example 1] A commercially available product, HEC2, was purchased and used as a viscosity modifier.
[0059] [Comparative Example 2] A commercially available product, HEC1, was purchased and used as a viscosity modifier.
[0060] [Measurement method] (viscosity) The samples were prepared by mixing the polymer nanofibers with water so that the polymer nanofiber content was 5% by mass. The viscosity of the samples containing the polymer nanofibers of each example was measured using a rheometer (HAAKE's "MARS60" product). The viscosity was measured under the following four conditions. μ1: Temperature 25℃, shear rate 0.1s -1 μ2: Temperature 25℃, shear rate 100s -1 μ3: Temperature 80℃, shear rate 0.1s -1
[0061] (Tg of solvophobic block) Based on the copolymer composition of the solubility block shown in Table 1, the glass transition temperature Tg (°C) of the copolymer was calculated using the following Fox equation. 1 / (273+Tg)=Σ{W i / (273+Tg i )} W i : mass fraction of monomer i Tg i : Tg (℃) of homopolymer of monomer i The glass transition temperature of the homopolymer is a value using the values described in "Polymer Handbook, 4th Edition, John Wiley & Sons."
[0062] [Table 1]
[0063] As shown in Table 1, the μ3 / μ1 values were lower in Examples 1 to 6 than in Comparative Examples 1 and 2. The viscosity control effect by temperature conditions was more significant in Examples 1 to 6 than in Comparative Examples 1 and 2. In addition, as shown by the μ2 / μ1 values in Examples 1 to 6, it can be confirmed that the viscosity also changes when the shear force conditions are changed.
[0064] 3 shows the shear viscosity characteristics of a sample containing the polymer nanofiber of Example 1. The glass transition temperature of the lyophobic core of the polymer nanofiber of Example 1 is 27° C. It can be seen that as the measurement temperature increases to 40° C., 60° C., and 80° C., the viscosity tends to decrease under a constant shear force condition.
[0065] 4 shows the shear viscosity characteristics of a sample containing the polymer nanofiber of Example 2. The glass transition temperature of the lyophobic core of the polymer nanofiber of Example 2 is 47°C. When the measurement temperature is 40°C, the decrease in viscosity under constant shear stress conditions is small. On the other hand, as the measurement temperature increases to 60°C and 80°C, the viscosity tends to decrease under constant shear stress conditions.
[0066] 5 shows the shear viscosity characteristics of a sample containing the polymer nanofiber of Example 3. The glass transition temperature of the lyophobic core of the polymer nanofiber of Example 3 is 27° C. It can be seen that as the measurement temperature increases to 40° C., 60° C., and 80° C., the viscosity tends to decrease under a constant shear force condition.
[0067] 6 shows the shear viscosity characteristics of a sample containing the polymer nanofiber of Example 4. The glass transition temperature of the lyophobic core of the polymer nanofiber of Example 4 is 47°C. When the measurement temperature is 40°C, the decrease in viscosity under constant shear stress conditions is small. On the other hand, as the measurement temperature increases to 60°C and 80°C, the viscosity tends to decrease under constant shear stress conditions.
[0068] 7 shows the shear viscosity characteristics of a sample containing the polymer nanofiber of Example 5. The glass transition temperature of the lyophobic core of the polymer nanofiber of Example 5 is 71°C. When the measurement temperatures are 40°C and 60°C, the degree of decrease in viscosity is small. On the other hand, at 80°C, which is higher than the glass transition temperature of the lyophobic core, the degree of decrease in viscosity under constant shear force conditions is large.
[0069] 8 shows the shear viscosity characteristics of a sample containing the polymer nanofiber of Example 6. The glass transition temperature of the lyophobic core of the polymer nanofiber of Example 6 is 54°C. When the measurement temperature is 40°C, the decrease in viscosity is small. As the measurement temperature increases to 60°C and 80°C, the viscosity tends to decrease under constant shear force conditions.
[0070] From the results of the Examples shown above, it can be seen that, according to the polymer nanofibers of Examples 1 to 6, the viscosity is likely to decrease on the high side of the glass transition temperature of the lyophobic core, whereas the viscosity is unlikely to decrease on the low side of the glass transition temperature. Thus, it can be confirmed that the viscosity characteristics change based on the glass transition temperature of the lyophobic core. [Industrial Applicability]
[0071] According to the present invention, there is provided a viscosity modifier whose viscosity characteristics can be controlled by changing temperature conditions. [Explanation of symbols]
[0072] 1. Amphiphilic block copolymers 2. Hydrophobic blocks 3. Hydrophilic Block 10 Polymer nanofibers 20 Hydrophobic Core 30 Hydrophilic Shell
Claims
1. Contains polymer nanofibers having a core-shell morphology with a lyophobic core and a lyophilic shell, A viscosity modifier, the viscosity characteristics of which change when the temperature conditions are changed based on the glass transition temperature of the lyophobic core.
2. The viscosity modifier of claim 1 , wherein the polymer nanofibers are formed by self-assembly of an amphiphilic block copolymer having a lyophobic block and a lyophilic block.
3. The viscosity modifier according to claim 2, wherein the lyophobic block has at least one selected from the group consisting of units based on styrene, units based on n-butyl (meth)acrylate, units based on methyl (meth)acrylate, and units based on benzyl (meth)acrylate.
4. The viscosity modifier of claim 1 , wherein the polymer nanofibers are crosslinked.
5. A liquid composition comprising the viscosity modifier according to any one of claims 1 to 4 and a liquid medium.
6. A method for adjusting the viscosity of the liquid composition according to claim 5, comprising the steps of: A viscosity adjusting method comprising changing a temperature condition based on a glass transition temperature of the lyophobic core to thereby change a viscosity characteristic of the liquid composition.
7. The method for adjusting viscosity according to claim 6, further comprising changing the viscosity of the liquid composition by changing a shear force condition.
8. An ink comprising the viscosity modifier according to any one of claims 1 to 4.
9. The ink of claim 8 for use in an ink jet printer.
10. An ink-jet printer comprising the ink according to claim 9.
Citation Information
Patent Citations
Thickener-containing abrasive-grain slurry and process for producing same
WO2016111165A1